2017
DOI: 10.14302/issn.2324-7339.jcrhap-17-1679
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an External Quality Assessment Program for HIV Testing in Tigray North Ethiopia 2016

Abstract: Background: Point-of-care diagnostic tests (POCTs) are increasingly used in both developing and developed countries. They allow same day testing and treatment at remote locations where no laboratory support is available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
4
0
0
Order By: Relevance
“…Despite a correct nal report of the HIV DTS PT samples, 15 % were not considered as acceptable due to failure to adhere to the NHTA. This nding is comparable to different studies conducted in Addis Ababa and Tigray region, Ethiopia which revealed a 10% and 12% failure to follow the NHTA respectively [9], [10] while another study in Kenya showed 12.9% non-adherence to the NHTA [11].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Despite a correct nal report of the HIV DTS PT samples, 15 % were not considered as acceptable due to failure to adhere to the NHTA. This nding is comparable to different studies conducted in Addis Ababa and Tigray region, Ethiopia which revealed a 10% and 12% failure to follow the NHTA respectively [9], [10] while another study in Kenya showed 12.9% non-adherence to the NHTA [11].…”
Section: Discussionsupporting
confidence: 87%
“…The objective assessment result that 64% of those who got supportive supervision versus about 36% of those with no suppervision scored acceptable result again emphasizes the need for due considerations of EQA to any testers in general and during task shifting in particular to ensure quality HIV rapid testing and scaling up of the HIV testing service to meet the rst 95% goal of UNAIDS by 2030 [1].On the other hand, in relation to facility conditions, 36% of testing sites did not have dedicated area (table/bench) for conducting HIV rapid test, 31% were without disinfectant for decontamination, 35% had no clean water supply for hand washing, while 14% did not have sharps container to dispose of sharps. These nding seem to be comparable with ndings conducted on 145 testing sites in Tigray which indicated that 41% of testing sites had no designated area for conducting HIV rapid test and 40% had no clean water for hand washing [10].…”
Section: Discussionsupporting
confidence: 76%
“…Despite a correct final report of the HIV DTS PT samples, 15% were not considered as acceptable due to failure to adhere to the NHTA. This finding is comparable to different studies conducted in Addis Ababa and Tigray region, Ethiopia which revealed a 10% and 12% failure to follow the NHTA respectively [ 8 , 9 ] while another study in Kenya showed 12.9% non-adherence to the NHTA [ 10 ].…”
Section: Discussionsupporting
confidence: 86%
“…The objective assessment result that 64% of those who got supportive supervision versus about 36% of those with no suppervision scored acceptable result again emphasizes the need for due considerations of EQA to any testers in general and during task shifting in particular to ensure quality HIV rapid testing and scaling up of the HIV testing service to meet the first 95% goal of UNAIDS by 2030 [ 1 ].On the other hand, in relation to facility conditions, 36% of testing sites did not have dedicated area (table/bench) for conducting HIV rapid test, 31% were without disinfectant for decontamination, 35% had no clean water supply for hand washing, while 14% did not have sharps container to dispose of sharps. These finding seem to be comparable with findings conducted on 145 testing sites in Tigray which indicated that 41% of testing sites had no designated area for conducting HIV rapid test and 40% had no clean water for hand washing [ 9 ].…”
Section: Discussionsupporting
confidence: 85%